2017
DOI: 10.3390/ijerph14121551
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Influenza Vaccine Acceptance among Pregnant Women in Zhejiang Province, China: Evidence Based on Health Belief Model

Abstract: Background: Reasons for acceptance of seasonal influenza vaccine (SIV) vaccination among pregnant women in China are poorly understood. We assessed the intention to accept SIV among pregnant women in Zhejiang province, by using a self-administrated structured questionnaire developed on the basis of health belief model (HBM). Methods: From 1 January to 31 March 2014, pregnant women with ≥12 gestational weeks who attended antenatal clinics (ANCs) at public hospitals in 6 out of 90 districts were surveyed using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 24 publications
5
42
2
Order By: Relevance
“…Our multivariable analysis taking into account both providers’ and women's characteristics revealed that pregnant women who received a recommendation from their attending physicians were more than twice as likely to receive the vaccine. This finding is consistent with other studies that demonstrated providers’ recommendation to be the most striking influencer with as much as 100‐fold increase in the likelihood of vaccination in pregnant women they cared for . We also found that physician self‐report of how frequently they recommended influenza vaccination to pregnant women in the past was not predictive of their recommendation during the visit as reported by the women.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our multivariable analysis taking into account both providers’ and women's characteristics revealed that pregnant women who received a recommendation from their attending physicians were more than twice as likely to receive the vaccine. This finding is consistent with other studies that demonstrated providers’ recommendation to be the most striking influencer with as much as 100‐fold increase in the likelihood of vaccination in pregnant women they cared for . We also found that physician self‐report of how frequently they recommended influenza vaccination to pregnant women in the past was not predictive of their recommendation during the visit as reported by the women.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with other studies that demonstrated providers' recommendation to be the most striking influencer with as much as 100-fold increase in the likelihood of vaccination in pregnant women they cared for. [46][47][48][49][50][51] We also found that physician self-report of how frequently they recommended influenza vaccination to pregnant women in the past was not predictive of their recommendation during the visit as reported by the women. There was also no association between self-vaccination and recommendation for pregnant women to vaccine.…”
Section: Con Clus Ionsmentioning
confidence: 64%
“… 49 , 50 One study conducted before the COVID-19 pandemic noted the significant associations between Perceived Threat or Risk, Barriers, and Cues to Action when determining flu or H1N1 vaccine intention, while another study focused on domains related to knowledge and attitudes towards the flu vaccine. 51 , 52 , 53 A recent study testing HBM with willingness to receive COVID-19 vaccine displayed that Perceived Benefits were significantly related to a “definite intention.” 50 Our study confirmed the role of Perceived Benefits and Perceived Barriers on the Vaccine Intention for both flu and COVID-19 vaccines. One published study used the HBM for vaccine intention among students for A/H1N1 influenza and reported that with similar predictors to this study, a calculated pseudo R 2 of 0.475 was significantly explained by Perceived Risk, Susceptibility, Seriousness, Barriers, and number of flu shots in the last 5 years.…”
Section: Discussionmentioning
confidence: 99%
“…In the already mentioned Italian surveys, 21% pregnant women expressed their willingness to get vaccinated for pertussis 14 and for influenza. 16 Studies in other countries reported that the values of those who would get vaccine against influenza ranging from 34.5% in the United States 8 to 76.3% in China, 19 whereas against pertussis a value of 89% has been observed in Canada. 12 Vaccination acceptability in the present study was significantly influenced by the negative beliefs about the safety of the vaccinations, since this willingness was significantly lower among the pregnant women who felt that the recommended vaccines administered during pregnancy were very dangerous for them and for their unborn child.…”
Section: Discussionmentioning
confidence: 99%